Peran Pendidikan Islam dalam Pemberdayaan Perempuan dan Pencegahan Woman Trafficking di Indonesia - Irham Abdul Haris (Attractive : Innovative Education Journal, 2024)
Human trafficking, especially women (woman trafficking), is essentially slavery in modern times. Trafficking can occur as a result of child adoption, money loans, unregistered marriages, promises of interesting work, low education and insight, working conditions and wages that have not been standardized. In responding to trafficking, Islam through education clearly rejects and offers several solutions so that humanity, especially women, is free from the practice of human trafficking. Islam teaches dharuriyatu khamsin (five human rights), consisting of maintaining the rights of religion, life, reason, property, lineage and honor. The role of Islam through education is very important as a preventive measure, namely with knowledge, skills and attitudes so that it is not easy to fall into human trafficking. Apart from that, Islam, through education, also seeks to empower women to have careers, so that they can live independently to meet their and their family's needs so that they do not easily fall into human trafficking